A Simplified Model for the Phase Composition Curve of Saline Soils Considering the Second Phase Transition. Issue 1 (15th January 2021) - Wang, Liyang; Liu, Jiankun; Yu, Xinbao; Wang, Tengfei; Feng, Ruiling
Abstract: Phase composition curves are the basis for the thermo‐hydraulic analysis of saline soil in cold regions. Two types of phase transition, namely, the water‐ice and solution‐crystal phase transitions, would occur in saline soils due to the variation in temperature and migration of moisture and solute, and the occurrence order of the two types of phase transition is governed by the initial salt and water content. This study proposed a conceptual model for the water phase composition curve in saline soils by simplifying the correlation between pore solution properties and soil grain. This model was subsequently applied to the analysis of phase composition characteristics and explained the occurrence of a second phase transition in saline soil. The model was validated by the experimental data from known soils and showed both good results and ease of use when compared to three previous models. The conceptual model provides a convenient and intuitive way to understand the phase composition characteristics of pore solution in saline soil in cold regions and is also easy to use in the thermo‐hydraulic analysis such as the prediction of unfrozen water content and solute concentration. Key Points: The correlation between the matrix effect and the freezing point depression is simplified A new conceptual model for the phase composition curve of saline soils is proposed and validated The phase composition characteristics of the pore solution of saline soils are analyzed